Hipercalcemia maligna secundária a carcinoma de saco anal em cão: a importância do reconhecimento das síndroems paraneoplásicas - Jark, Paulo César [UNESP] (2011)
The anal sac carcinoma is an uncommon neoplasm in dogs originates in the apocrine glands located inside the anal sac. The main paraneoplastic syndrome related to this tumor is malignant hypercalcemia. We describe a case of carcinoma of anal sac with malignant hypercalcemia in which manifestations of paraneoplastic syndrome resulting clicks were essential for the correct diagnosis.